2021
DOI: 10.1007/s00296-021-04965-6
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab treatment in severe COVID-19: a multicenter retrospective study with matched controls

Abstract: Coronavirus disease-2019 (COVID-19) associated pneumonia may progress into acute respiratory distress syndrome (ARDS). Some patients develop features of macrophage activation syndrome (MAS). Elevated levels of IL-6 were reported to be associated with severe disease, and anti-IL-6R tocilizumab has been shown to be effective in some patients. This retrospective multicenter case–control study aimed to evaluate the efficacy of tocilizumab in hospitalized COVID-19 patients, who received standard of care with or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Regarding IL-6 blockade with tocilizumab in COVID-19-associated MAS, the results are controversial. Some studies have reported that treatment with tocilizumab contributes to reduced mortality and favorable outcomes [144,145]. Conversely, another study noted that tocilizumab demonstrated limited efficacy for COVID-19-related MAS [146].…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Regarding IL-6 blockade with tocilizumab in COVID-19-associated MAS, the results are controversial. Some studies have reported that treatment with tocilizumab contributes to reduced mortality and favorable outcomes [144,145]. Conversely, another study noted that tocilizumab demonstrated limited efficacy for COVID-19-related MAS [146].…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Overzealous immune responses associated with MAS, may be driving COVID-19 related ARDS ( 21 ). There has been research shows that treatment of MAS, such as the use of tocilizumab and the combination of tocilizumab and steroids, significantly reduced the intubation or death of severe patients ( 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 In cases of severe COVID-19 pneumonia, patients who received TCZ were shown to have better outcomes, and retrospective observational cohort studies revealed an immediate decrease in fever, decreased need for oxygen therapy and mechanical ventilation, as well as an improvement in lung symptoms. [10][11][12][13][14]…”
Section: Introductionmentioning
confidence: 99%